1974
DOI: 10.1159/000122269
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Adrenal Sensitivity to ACTH in the Vasopressin-Deficient (Brattleboro) Rat

Abstract: We examined the role of vasopressin (VP) in brain-adrenal function by comparing the plasma corticosterone concentrations of rats genetically deficient in VP [Brattleboro rats, homozygous for diabetes insipidus (Dl-homo)] with those of control animals. Rats were subjected to stressful situations and exogenous ACTH, and their adrenal sensitivity to ACTH was assessed in vitro. Some Dl-homo rats were treated chronically with VP and their plasma corticosterone concentrations were examined during stress. We confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
15
2

Year Published

1975
1975
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(22 citation statements)
references
References 4 publications
5
15
2
Order By: Relevance
“…However, this explanation cannot explain the lack of difference in corticosterone in the face of different ACTH concentrations in the studies that incorporated serial blood sampling. Enhanced adrenal gland sensitivity to ACTH could have provided a simple explanation; however, a decreased adrenal sensitivity to ACTH in di/di animals was observed and is also supported by previous in vitro (Wiley et al 1974) and in vivo (Brudieux et al 1986) studies. Similar dissociations were Figure 6 Sensitivity of the anterior pituitary to CRH.…”
Section: Discussionsupporting
confidence: 75%
“…However, this explanation cannot explain the lack of difference in corticosterone in the face of different ACTH concentrations in the studies that incorporated serial blood sampling. Enhanced adrenal gland sensitivity to ACTH could have provided a simple explanation; however, a decreased adrenal sensitivity to ACTH in di/di animals was observed and is also supported by previous in vitro (Wiley et al 1974) and in vivo (Brudieux et al 1986) studies. Similar dissociations were Figure 6 Sensitivity of the anterior pituitary to CRH.…”
Section: Discussionsupporting
confidence: 75%
“…Impairment of stress responses has been reported by McCann et al [9], Yates et al [30] and Wiley et al [28], while normal functions were observed by Arimura et al [3]. A reduced adrenal response to ACTH in HO-DI rats has also been found [28]. However, the present experiments suggest that impairment of the pituitary-adrenal response in HO-DI rats may pnmarily depend on a disturbance in the psychological response to stress.…”
Section: Discussionsupporting
confidence: 54%
“…Several authors have investigated the pituitary-adrenal function of HO-DI rats. Impairment of stress responses has been reported by McCann et al [9], Yates et al [30] and Wiley et al [28], while normal functions were observed by Arimura et al [3]. A reduced adrenal response to ACTH in HO-DI rats has also been found [28].…”
Section: Discussionmentioning
confidence: 87%
“…A spontaneous point mutation resulted in an altered AVP precursor which was unable to enter the secretory pathway (Evans et al, 2000, Surget andBelzung, 2008). As a result, homozygous AVP-deficient Brattleboro rats (KO) show diminished HPA axis responses to different acute stressors (Wiley et al, 1974, Conte-Devolx et al, 1982, Fink et al, 1992, accompanied by reduced depressive-and anxiety-like behavioral profile (Mlynarik et al, 2007). More specifically, AVP-deficient rats showed higher preference for a sweet solution, spent considerably shorter time immobile in the FS test and less time self-grooming on the elevated plus maze (EPM) accompanied by a higher level of dexamethasone-induced suppression of corticosterone response to restraint stress.…”
mentioning
confidence: 99%